An investigation of the real effects of government expenditures - Arroyo, Gloria Macapagal-, 1947- (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1987)
The paper examines the macroeconomic effects of government expenditures. The possible crowding-out effects of government expenditures on private consumption are investigated under the notion that the possible benefits of government spending, as well as the changes in disposable income due to tax changes are both perceived by people - a case of two sided rationality. The discussion takes off from the empirical work of Feldstein in defense of the multiplier effect of government purchases, and that of Kormendi about the crowding-out effect of government expenditures on consumption.